Gaya Belajar Siswa Bagi Burhanuddin Zarnuji - Hilman Haroen (Ulumuddin : Jurnal Ilmu-ilmu Keislaman, 2018)
This paper explores the learning styles in classical Islamic education. The focus is on the learning process recommended by BurhanuddinZarnuji in his famous work of Ta'līm Al-Muta'allim. Through literature research, it is known that the learning styles developed are still not as they are now expected to be. More established classifications and categorizations are still in need of further steps.